What happens online stays online? Segment-specific online and offline effects of banner advertisements - LOBSCHAT, Lara (Institutional Knowledge at Singapore Management University, 2017)
Many firms allocate increasing parts of their advertising budgets to banner advertising. Yet, for firms that predominantly sell offline, existing research provides little guidance on online advertising decisions. In this study, the authors analyze the impact of banner advertising on consumers' online and offline behavior across multiple distinct campaigns for one focal firm, which predominantly sells through the offline channel. Results suggest that banner and TV advertising increase website visit incidence for consumers who had not visited the focal firm's website in the previous four weeks (non-recent online consumers). For these consumers, banner and TV advertisements indirectly increase offline sales through website visits. For consumers who have visited the firm's website in the previous four weeks (recent online consumers), the authors find evidence for a cross-campaign, brand-building effect of banner advertising, and TV ads also directly affect offline purchases. Overall, the findings indicate that for firms which predominantly (or even exclusively) sell offline, banner advertising is most suitable to generate awareness for a firm's new products among non-recent online consumers, and to build their brand(s) among recent online consumers.